Introducción a los análisis espaciales con énfasis en modelos de nicho ecológico - Cuervo Robayo, Angela P. (2017)
In 2016, we implemented a system of seminars for teaching, in open accessvideo format available via the Internet, aiming to show in Spanish and in simple form the conceptual bases and applications of ecological niche modeling in studies of ecology, biological conservation, epidemiology, and agro-biodiversity, as well as its implementation for designing public policies for natural resources. Each seminar was developed by one or several experts discussing concepts, methods, and tools available to construct species distribution models. This manuscript assembles the abstracts for each of the seminars online, providing key references for each topic and links to the corresponding videos. The videos are available freely via YouTube or in .mp4 format by request.